Dental derived stem cell conditioned media for hair growth stimulation - Gunawardena, Tarini Nawamalie Abeysinghe; Masoudian, Zeinab; Rahman, Mohammad Tariqur; Ramasamy, Thamil Selvee; Ramanathan, Anand; Abu Kasim, Noor Hayaty (Public Library of Science, 2019)
Alopecia is a clinical condition caused by excessive hair loss which may result in baldness, the causes of which still remain elusive. Conditioned media (CM) from stem cells shows promise in regenerative medicine. Our aim was to evaluate the potential CM of dental pulp stem cells obtained from human deciduous teeth (SHED-CM) to stimulate hair growth under in vitro and in vivo conditions. SHED and hair follicle stem cells (HFSCs) (n = 3) were cultured in media combinations; i) STK2, ii) DMEM-KO+10% FBS, iii) STK2+2% FBS and profiled for the presence of positive hair growth-regulatory paracrine factors; SDF-1, HGF, VEGF-A, PDGF-BB and negative hair growth-regulatory paracrine factors; IL-1α, IL-1β, TGF-β, bFGF, TNF-α, and BDNF. The potential of CM from both cell sources to stimulate hair growth was evaluated based on the paracrine profile and measured dynamics of hair growth under in vitro conditions. The administration of CM media to telogen-staged synchronized 7-week old C3H/HeN female mice was carried out to study the potential of the CM to stimulate hair growth in vivo. SHED and HFSCs cultured in STK2 based media showed a shorter population doubling time, higher viability and better maintenance of MSC characteristics in comparison to cells cultured in DMEM-KO media. STK2 based CM contained only two negative hair growth-regulatory factors; TNF-α, IL-1 while DMEM-KO CM contained all negative hair growth-regulatory factors. The in vitro study confirmed that treatment with STK2 based media CM from passage 3 SHED and HFSCs resulted in a significantly higher number of anagen-staged hair follicles (p<0.05) and a significantly lower number of telogen-staged hair follicles (p<0.05). Administration of SHED-CM to C3H/HeN mice resulted in a significantly faster stimulation of hair growth in comparison to HFSC-CM (p<0.05), while the duration taken for complete hair coverage was similar for both CM sources. Thus, SHED-CM carries the potential to stimulate hair growth which can be used as a treatment tool for alopecia.